Novel morphologies for laterally decorated metaparticles: molecular dynamics simulation - Slyusarchuk, A.Y.; Ilnytskyi, J.M. (Condensed Matter Physics, 2014)
We consider a mesoscale model for nano-sized metaparticles (MPs) composed of a central sphere decorated by polymer chains with laterally attached spherocylinder. The latter mimics the mesogenic (e.g., cyanobiphenyl) group. Molecular dynamics simulations of 100 MPs reveal the existence of two novel morphologies: uColh (hexagonal columnar arrangement of MPs with strong uniaxial order of LC groups collinear to the columns axis) and wColh (the same arrangement of MPs but with weak or no LC order). Collinearity of the LC director and the columnar axis in uColh morphology indicates its potentially different opto-mechanical response to an external perturbation as compared to the columnar phase for the terminally attached LC groups. Preliminary analysis of the structures of both phases is performed by studying the order parameters and by visualisation of the MPs arrangements. Different mechanisms for the LC groups reorientation are pointed out for the cases of their terminal and lateral attachment. Розглянуто мезоскопiчну модель нанорозмiрних метачастинок (МЧ), якi складається iз центральної сфери, декорованої полiмерними ланцюжками iз бiчним приєднанням сфероцилiндрiв. Останнi описують
мезогеннi (напр. цианобiфенiльнi) групи. Виконанi симуляцiї 100 МЧ за допомогою молекулярної динамiки вказують на iснування двох нових морфологiй: uColh (iз гексагональним стовпцевим впакуванням
МЧ та сильним одновiсним впорядкуванням рiдкокристалiчних груп колiнеарно до осi стовпцiв) та wColh
(iз тим же впорядкування МЧ але слабким або вiдсутнiм рiдкокристалiчним впорядкуванням). Колiнеарнiсть директора та осi симетрiї стовпцевої фази у морфологiї uColh вказує на її потенцiйно iншу оптикомеханiчну реакцiю на зовнiшнє збурення порiвняно iз стовпцевою фазою для моделi iз кiнцевим приєднанням рiдкокристалiчних груп. Попереднiй аналiз структур обох фаз виконано шляхом дослiдження
параметрiв порядку та вiзуалiзацiєю розташування МЧ. Вказано на роль рiзних механiзмiв реорiєнтацiї
мезогенiв залежно вiд способу їх приєднання.